(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Historical and demographic processes have significantly influenced the transformation from traditional to modern family, changing its structure, functions, partnerships, as well as parenting and child rearing, perceptions of marriage, divorce, birth-rates, etc. After the Industrial revolution, the nuclear family became the dominant model of family in Europe and it is still prevailing in the Macedonian contemporary society. Social changes such as globalization, individualization, secularization, and the dynamics of modern living have led to new family forms that reflect modern societies. This paper will present a brief analysis of family structures, the transformation from traditional to modern family and it will discuss new family models. Particularly, it will focus on cohabitation, multi-ethnic families and same-sex relationships in the Republic of North Macedonia by presenting the results of a qualitative research on perception of new family models in North Macedonia conducted during 2019.